2020
DOI: 10.29244/jtcs.7.03.97-103
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Content Below 33.7% Progressively Reduces the Latex Yield of Rubber PB 60, A Study in Sembawa, South Sumatra, Indonesia

Abstract: Rubber is one of the economically important tropical trees that produces natural rubber, an essential industrial raw material in Indonesia. In general, rubber can grow well in areas with 1,500 - 3,000 mm rainfall per year that evenly distributed round the year. During the dry season, water availability is reduced so that water becomes a limiting factor for the growth and production of the rubber tree. This paper aimed to determine minimum soil water content that must be maintained to preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…On the contrary, the highest rubber yield was generated in the same month with the highest soil water content (May). This finding was in accordance with previous research which reported that the occurrence of dry season resulted in decrease of soil water content as well as rubber yield [2,7,19]. Furthermore, the same pattern of the fluctuation of soil water content and rubber yield indicated that rubber yield can be predicted using soil water content data.…”
Section: Formulation Of the Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, the highest rubber yield was generated in the same month with the highest soil water content (May). This finding was in accordance with previous research which reported that the occurrence of dry season resulted in decrease of soil water content as well as rubber yield [2,7,19]. Furthermore, the same pattern of the fluctuation of soil water content and rubber yield indicated that rubber yield can be predicted using soil water content data.…”
Section: Formulation Of the Modelsupporting
confidence: 92%
“…However, in some areas in Indonesia, the rainfall is not evenly distributed, hence drought usually occurs several months in a year. The drought causes a decrease in rubber yield [2,3]. However excessive water in the rubber field also decreases rubber yield, because the root zone is inundated by waterlogging [4].…”
Section: Introductionmentioning
confidence: 99%
“…This consequently led to heightened rubber growth, elevated latex yields, and improved quality of the latex yield. Ardika and Cahyo (2020), identified a positive correlation between rainfall and the production of the PB 260 rubber clone, 0.89 0.03 tn Note: ** significant correlation at the 0.01 level; * significant at the 0.05 level; and tn the correlation is not significant spanning from one to 3-month lead time. Study showed that latex yield increased during the rainy season under irrigation as reported from a field experimental plot in Thailand (Mak et al, 2008).…”
Section: Resultsmentioning
confidence: 97%
“…In the wet zone area of Sri Lanka, a reduction in rainfall produced rubber yield, which was 35% lower compared to normal climate condition (Alahacoon and Giriraj, 2022). In dry months, rubber plants experience high temperatures and insufficient rainfall causing moisture stress, which is the limiting factor for maximum latex yield (Kunjet et al, 2013;Ardika and Cahyo 2020). Moisture depletion was associated to reduced growth and latex yield (Raj et al, 2005).…”
Section: Resultsmentioning
confidence: 99%